Eggshell waste separation process assisted with pressure‐vacuum: Process conditions and optimization. Issue 1 (19th December 2022) - Chi, Yuan; Lin, Mengmeng; Zuo, Daming; Wang, Hailing; Chi, Yujie
Abstract : Abstract: Eggshells and eggshell membranes have high‐value recycling applications and have been widely used in pharmaceutical, chemical, and food research. The separation of eggshells and eggshell membranes is a prerequisite to efficiently using both. Therefore, the pressure‐vacuum experiment equipment was designed. In this study, research on the separation of eggshells and eggshell membranes from waste eggshells using the pressure‐vacuum experiment equipment was carried out. The flash evaporation experiment process controlled the experimental factors to obtain a sufficient moisture content between the eggshell and eggshell membrane with vigorous flash evaporation. The effects of experimental factors such as superheat (5–10°C), temperature (50–70°C), initial pressure (0.6–0.8 MPa), pressurization time (0–40 min), and particle size (6–8 mm) on the separation rate were investigated in the pressure‐vacuum experiment process. Through single‐factor and orthogonal experiments, it was found that the separation rate was most affected by changes in temperature, initial pressure, and particle size, followed by the interaction of temperature and particle size. The experimental results suggested that the optimum separation of eggshell membranes from eggshells was achieved at higher superheat, higher temperature, higher initial pressure, medium pressurization time, and smaller particle size. Through optimization by response surface methodology, the optimal conditions for the separation of eggshells and eggshell membranes using the flash evaporation method were determined as 15°C of superheat, 70°C of temperature, 0.8 MPa of initial pressure, and 6 mm of particle size. Flash evaporation method is an effective and environmentally friendly method, which provides a new solution for the recycling of waste eggshells. Practical Application: In this study, pressure‐vacuum experiment equipment was utilized to reuse of waste eggshells, and an innovative and environmentally friendly method of eggshell membrane and eggshell separation was established. The pressure‐vacuum experiment equipment has a simple structure and low energy consumption. The results of flash evaporation experiments are instructive for further in‐depth studies on the separation of eggshells and eggshell membranes. Furthermore, the separation of eggshells and egg membranes by flash evaporation is of great research value. Most importantly, the separated eggshells and eggshell membrane are available for high‐value applications in food, chemical, and biological fields.